1977
DOI: 10.1084/jem.145.5.1188
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between surface immunoglobulin isotype and immune function of murine B lymphocytes. I. Surface immunoglobulin isotypes on primed B cells in the spleen.

Abstract: We investigated the ability of IgM-, IgD-, and IgG-bearing cells from the spleens of (BALB/c x C57BL/Ka)F1 mice primed to dinitrophenyl-bovine serum albumin (DNP-BSA) to restore the adoptive secondary anti-BSA and anti-DNP antibody responses. A rabbit anti-mouse IgD antiserum was prepared and the specificity documented by radioimmunoprecipitation, and cell surface staining. Purified populations of IgM-, IgD-, and IgG-bearing cells were prepared by immunofluorescent staining with isotype-specific reagents, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
33
0

Year Published

1977
1977
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 12 publications
(12 reference statements)
13
33
0
Order By: Relevance
“…This, in turn, was a confirmation of previous findings in which, serum responses to another hapten, DNP, was also dominated by IgM following oral immunizations with DNP-KLH plus CT adjuvant [13]. Early studies also suggested a strong role of IgM in the generation or maintenance of memory following systemic immunizations [15][16][17]. In general, relatively little information is available on the isotype distribution of serum Ig or Ig-secreting cells in various tissues in long-term (over 3 months) memory studies.…”
Section: Discussionsupporting
confidence: 84%
“…This, in turn, was a confirmation of previous findings in which, serum responses to another hapten, DNP, was also dominated by IgM following oral immunizations with DNP-KLH plus CT adjuvant [13]. Early studies also suggested a strong role of IgM in the generation or maintenance of memory following systemic immunizations [15][16][17]. In general, relatively little information is available on the isotype distribution of serum Ig or Ig-secreting cells in various tissues in long-term (over 3 months) memory studies.…”
Section: Discussionsupporting
confidence: 84%
“…Rabbit anti-6 was judged to be monospecific by published criteria (18), including: (i) a single peak on sodium dodecyl sulfate/polyacrylamide gel electrophoresis after reaction with a lysate of iodinated splenocytes; (ii) immunofluorescent staining of the predicted numbers of cells from various lymphoid tissues; (iii) inability to stain splenocytes after their treatment with either anti-Ig or allotypic (19) anti-6; and (iv) independent capping of surface molecules on splenocytes with anti-6 and anti-A. Chromatographically purified fractions of normal rabbit serum (NRS), anti-,q, anti-Ig, or a 30% (NH4)2SO4 saturation precipitate of anti-6 was used for in vitro cell culture.…”
Section: Methodsmentioning
confidence: 99%
“…With the background knowledge of IgD being involved in B lymphocyte differentia tion events [15] and a precursor of IgG cells in the mouse [24] we designed several ex periments to measure immunoglobulin syn thesis by the lymphocytes of PR patients. As shown in table IV the level of serum IgM, IgG, IgD, IgA, IgE in PR during the acute and convalescent stages of the disease are similar to that of normal individuals with a normal frequency of IgD and/or IgM-bearing cells.…”
Section: Discussionmentioning
confidence: 99%